Survei Pelaksanaan Proses Pembelajaran Penjasorkes Pada Siswa di Sekolah Luar Biasa ( SLB ) - Lukman, Duladi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to investigate the implementation of the learning system ofphysical education and health in students in special schools (SLB) N 2 in Pemalang 2014.This research method is a qualitative research, which means that the issues discussed in theresearch aims to create a description, picture or painting in a systematic, factual and accurateinformation on the facts. Results from this study can be explained that, syllabus and lessonplans are available at the school and has been modified to suit the abilities and conditions sothat students can follow the lesson well. The conclusion of this study, that the teacher continuesto provide motivation and reinforcement during the learning process of physical educationfor mentally disabled children as to provide motivation and reinforcement will increase theenthusiasm and spirit of the child.